Financial conditions, business cycle fluctuations and growth at risk - Andrea Falconio; Simone Manganelli (European Central Bank (ECB), 2020)
We study the macroeconomic consequences of financial shocks and increase in economic risk using a quantile vector autoregression. Financial shocks have a negative, but asymmetric impact on the real economy: they substantially increase growth at risk, but have limited impact on upside potential. The impact of financial shocks is explained away after controlling for economic risk (measured by the interquantile range). The effects are economically relevant. Bad economic environment, characterized by negative real and financial shocks, has a highly skewed impact on business cycle fluctuations, leading to a peak reduction of monthly industrial production by more than 2%. In comparison, positive real and financial shocks in a good economic environment have limited effect on upside potential of the economy
Keywords: C32; C53; E32; E44; 330; Risk; uncertainty; financial conditions; quantile regression